DOS CABIDES DE EMPREGO AOS CABIDES DO CONHECIMENTO: UM CASO DE PARCERIA ENTRE O INSTITUTO GENERAL MOTORS E A ESCOLAMUNICIPAL DE ENSINO PROFª. ALCINA DANTAS FEIJÃO NO DESENVOLVIMENTO DA RESPONSABILIDADE SOCIAL EMPRESARIAL - Costa, Magda Mônica Pereira da (2012)
Brazilian authorities, until few years ago, did not consider in their agenda of priorities the education as the main focus to the economic growth, perhaps because they did not believe that with the stability of money, economy opening and other factors, they would need qualified people to maintain the productive capacity. So, nowadays, the country tries to correct this situation investing on education, adding new technologies in the productive process, being necessary a task force able to learn and develop new techniques. Nowadays, Brazil sustains one of the lowest unemployment taxes, however, several companies suffer with the lack of qualified people, therefore it is necessary to train employees and as a consequence there is an increase in the costs. The companies try to deal with the lack of qualified people investing in programs such as trainees, hiring foreigner workers, creating corporative universities, and in some cases, the companies become close to the education net, aiming to prepare young people to the domain of new technologies, promoting their refinement in their acting area, avoiding the unbalance between theory and practice. The entrepreneur organizations conscious of their role, begin to understand that the so desired prosperity does not mean valuables invoices or simply the quantity of products sold. They become aware to the creation and adaptation of corporate citizens that through their social actions try to develop solidary activities. In this context, this study has as general aim to analyze the Social Entrepreneurial Responsibility under partnership view with schools (partnership between General Motors do Brasil, through its social arm -the Instituto General Motors end the Escola Municipal de Ensino Profª. Alcina Dantas Feijão da Cidade de São Caetano do Sul). The partnership is materialized through the program Jovem Empreendedor or Fábrica de Cabides . The purpose of this program is to bring the students the enterprise spirit and stimulate the rise of future enterprisers. With specific aims it has the following purposes: a) study the partnership between companies and developing schools of RSE; b) understand the reasons why the company and the schools materialize the partnership and its expectations; c) identify possible changes occurred in the school and attributed to the partnership process. From these aims, through the method of case study, it became evident that initiatives of partnership can revert into better quality of education, which makes possible the development of competence and necessary abilities to insert in the labor market with a citizen dimension.